Բառերի իմաստափոխության մի քանի հիմունքներ - Սուքիասյան, Քնարիկ
В данной работе рассматриваются смысловые изменения слов. Это происходит в результате исторического развития языка и в основном в связи с употреблением слов в переносном смысле.The change of the meaning of the words is discussed in this article. These changes are practiced as consequences of the historical development of a language and generally because of the metaphorical use of the words.
Keywords: Լեզվաբանություն